Perbedaan Model dan Teori dalam Ilmu Komunikasi - Bambang A. S. (Bina Nusantara University, 2014)
This article aims to describe differences in models and theories of communication and their respective roles. Many students of Communication Studies do not really care because it was considered too elementary. Students tend to focus on the